2015
DOI: 10.1007/s10493-015-9998-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of predation risk on spermatophore deposition rate of the eriophyoid mite, Aculops allotrichus

Abstract: Eriophyoids are minute herbivores in which males deposit spermatophores on a substrate while females, independent of the presence of males, pick up sperm (sex dissociation). Their most dangerous enemies are phytoseiid mites. Eriophyoids can successfully avoid the predation by, e.g., forming galls in which they live, by inhabiting narrow spaces on plants, or by climbing up leaf trichomes for the time of quiescence. All these behaviours, however, are fixed and independent of the actual risk of predation. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…These results were opposite to our hypothesis that males ejaculate more sperm and females become choosier and remove more sperm when they are exposed to a high predation risk. In the eriophyoid mite, Aculops allotrichus, in which males deposit spermatophores on a substrate while females pick up sperm regardless of the presence of males, the males deposited fewer spermatophores when the predation risk was high (Michalska 2016). Reported results for precopulatory mate choice are similar to our results (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…These results were opposite to our hypothesis that males ejaculate more sperm and females become choosier and remove more sperm when they are exposed to a high predation risk. In the eriophyoid mite, Aculops allotrichus, in which males deposit spermatophores on a substrate while females pick up sperm regardless of the presence of males, the males deposited fewer spermatophores when the predation risk was high (Michalska 2016). Reported results for precopulatory mate choice are similar to our results (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…However, in further investigations by [21], only four out of ten of the tested eriophyoid species became more active on non-host plants. Recent observations on Aculops allotrichus (Nalepa) [25] and Aceria guerreronis Keifer [20] revealed that eriophyoids can also respond to the cues left on plants by predatory mites and heterospecific competitors. The eriophyoids of A. guerreronis sought refugia under floral bracts of the coconut when they were exposed to the cues of phytoseiids, Neoseiulus baraki (Athias-Henriot), or Amblyseilus largoensis (Muma) [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, they remained outside the refugium in the presence of the cues of the competitor, the tarsonemid mite Steneotarsonemus concavuscutum Lofego and Gondim Jr. Males of A. allotrichus also responded to predation risk and decreased their spermatophore deposition rate in the presence of cues from the phytoseiid mite Amblyseilus swirskii (Athias-Henriot) [25]. Interestingly, the presence of artificially pierced conspecifics did not elicit either movement of A. guerreronis to the safer sites [20] or changes in the spermatophore deposition rate in A. allotrichus males [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most research has focused on the impacts of predation risk on the behaviour of only phytophagous mites such as spider mites (Tetranychidae) (e.g. Grostal and Dicke 1998;Bowler et al 2012) and gall mites (Eriophyidae) (Michalska 2016). Little is known about the non-consumptive effects of predatory mites on other kinds of mites such as the stored product mite Tyrophagus putrescentiae (Schrank) (Acaridae).…”
mentioning
confidence: 99%